2009
DOI: 10.1073/pnas.0905118106
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinases mediate ligand-independent derepression of sumoylated progesterone receptors in breast cancer cells

Abstract: In advanced breast tumors, protein kinases are upregulated and steroid hormone receptors often function independently of ligand. Herein, we explored mechanisms of ligand-independent progesterone receptor (PR) activity. We showed previously that growth factorinduced phosphorylation of PR Ser-294 blocks PR Lys-388 sumoylation. SUMO-deficient mutant PR-B (K388R) thus provides a model receptor for the study of PR function in the context of high kinase activities. T47D cells stably expressing K388R PR-B exhibited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 34 publications
5
70
1
Order By: Relevance
“…Although the knowledge of their functions and mechanisms is still little, some studies have showed that they are also associated with breast cancer and other human cancers. The regulation of gene expression by phosphorylated and undersumoylated PRs is a novel form of hormone independent PR action that is predicted to contribute to breast cancer cell growth and survival (Daniel et al, 2009). Recent studies revealed that E3 ubiquitin ligases play important roles in breast carcinogenesis.…”
Section: The Other Histone Modifications In Breast Cancermentioning
confidence: 99%
“…Although the knowledge of their functions and mechanisms is still little, some studies have showed that they are also associated with breast cancer and other human cancers. The regulation of gene expression by phosphorylated and undersumoylated PRs is a novel form of hormone independent PR action that is predicted to contribute to breast cancer cell growth and survival (Daniel et al, 2009). Recent studies revealed that E3 ubiquitin ligases play important roles in breast carcinogenesis.…”
Section: The Other Histone Modifications In Breast Cancermentioning
confidence: 99%
“…23 However, few studies show that the expression of STC1 is not an independent and unfavorable prognostic factor for esophageal squamous cell carcinoma (ESCC). 27 …”
Section: Expression In Cancermentioning
confidence: 99%
“…26 Breast cancer growth is insensitive to progestins, and knockdown of STC1 inhibits proliferation of tumor cells expressing progesterone receptor (PR), suggesting that STC1 may play a potential role in therapy of breast cancer. 27 …”
Section: Proliferationmentioning
confidence: 99%
“…Subtle changes at the cellular level can have major effects. The phosphorylation and sumolyation of PR by intracellular mechanisms can impact PR action (Daniel and Lange, 2009). Fibroids are understood to be clonal in nature and thus may vary from one cell line to another.…”
Section: Evidence For the Cellular Mode Of Action: Uterine Proliferatmentioning
confidence: 99%